Topical Ointment Anredera cordifolia Leaves Ethanolic Extract-Loaded Nanochitosan Promotes Wound Healing in Hyperglycemic Rat - Alfatinnisa, Zalfa; Andriyan, Mohammad Wahyu; Saputra, Muhammad Ragil; Astuti, Endah Puji; Sunarno, Sunarno; Isdadiyanto, Sri; Subagio, Agus; Jaya, La Ode Irman (Universitas Negeri Semarang, 2024)
Wound healing in hyperglycemia patients is still a challenge in the medical field. Bioactive compounds of binahong leaf extract can support the wound healing process. Nanoencapsulation of the extract can avoid oxidation and optimize drug delivery to target tissues. This study aimed to analyze the effect of nanochitosan encapsulated binahong extract ointment (NEBE/Oint) on the percentage of wound healing, angiogenesis, collagen density, and epithelial thickness in hyperglycemic rats. This study used 80 mg/kg streptozotocin-induced hyperglycemia rats injured in the back area. Rats were divided into P0 (0,9% NaCl), P1 (10% povidone-iodine ointment (PI/Oint)), P2 (10% NEBE/Oint), P3 (20% NEBE/Oint), P4 (30% NEBE/Oint). Phytochemical screening of binahong leaves extract showed positive results for flavonoids, alkaloids, saponins, and tannins. NEBE particle size was 169 nm with a size distribution of 0.2 and a zeta potential value of -40,2 mV. The results showed NEBE ointment had a significant effect when compared with negative control on wound healing hyperglycemic rats. The conclusion is that nanochitosan drug delivery has the potential as an alternative wound treatment. The novelty of this study is the use of nanochitosan to accelerate wound healing in hyperglycemic rats. The results of this study are expected to become a reference for new wound-healing methods in the medical field.